Analysis of Mortality Risk Factors in Children with Pneumonia in RSUD Dr Soetomo Surabaya - Tutwuri Handayani; Retno Asih Setyoningrum (PT Dexa Medica, 2022)
Background: Pneumonia is one of the leading causes of under-five morbidity and mortality. We carried out a comprehensive study to identify risk factors contributing to both mortality and morbidity rate in children less than 5 years of age that were hospitalized with pneumonia. Objective: To evaluate mortality risk factors in children with pneumonia in RSUD Dr. Soetomo Surabaya. Methods: This is an analytic observational study using secondary data that was taken from medical record of hospitalized children with pneumonia between 2015-2018. Data was analysed using Chi-square test or Fisher’s exact test and logistic regression (p<0.05). Results: A total of 817 children with pneumonia were enrolled in this study. In children aged 2–59 months, the risk factors significantly associated with death included age, low birth weight, prematurity, breastfeeding status, pleural effusion, atelectasis, and comorbidity. Logistic regression revealed status of breastfeeding, pleural effusion, and comorbidities, influenced the mortality outcome of pneumonia. Conclusion: Nonexclusive breastfeeding, pleural effusion and comorbidities are the independent predictors of mortality in children with pneumonia. Thus, early identification and prompt management of these simple clinically recognizable predictors of death may help reduce mortality rate in such population.